Financing patterns of European SMEs: An Empirical Taxonomy - Alexandra Moritz; Joern H. Block; Andreas Heinz (European Investment Fund (EIF), 2015)
This EIF Working Paper takes a holistic approach to investigate SME financing patterns in Europe by performing a cluster analysis including 12,726 SMEs in 28 European countries. The results reveal that SME financing in Europe is not homogenous but that different financing patterns exist. The cluster analysis identifies six distinct SME financing types: mixed-financed SMEs, state-subsidised SMEs, debt-financed SMEs, flexible-debt-financed SMEs, trade-financed SMEs and internally-financed SMEs. These SME financing types differ according to the number of financing instruments used and the combinations thereof. Furthermore, the SME financing types can be profiled according to their firm-, product-, industry- and country-specific characteristics. Our findings can support policy makers in assessing the impact of policy changes on SME financing and in designing financing programs tailored to the specific needs of SMEs.
Keywords: 330